Landscape Response to Lateral Advection in Convergent Orogens Over Geologic Time Scales. Issue 8 (5th August 2019) - Eizenhöfer, Paul R.; McQuarrie, Nadine; Shelef, Eitan; Ehlers, Todd A.
Abstract: Convergent orogens exhibit high elevations and relief, features characteristic of active rock uplift, the latter influencing normalized channel steepness ( K sn ). In systems with significant horizontal displacement, K sn values and interfluves are elevated over a region of tens of kilometers and gradually decline in the direction of rock advection. To evaluate potential relationships between elevated K sn, a gradual decline in interfluve elevation (i.e., tapered topography), and lateral advection, we integrated kinematic models that simulate advection over a midcrustal ramp with a 2‐D surface processes model. Varying convergence rate, bedrock erodibility, and ramp angle, we tracked topographic evolution over time. The process of advection through the region of active rock uplift above a midcrustal ramp is preserved in the geomorphic record through transient legacy landscapes characterized by (i) high‐relief, advection‐parallel interfluves, (ii) tapered topography, (iii) elevated and gradually declining K sn values, and (iv) higher K sn in trunk relative to tributary streams likely reflecting the influence of increased sediment flux, elevated interfluves, and changes in drainage area. The width of legacy landscapes provides a minimum constraint on the total lateral displacement, controlled by the duration of ramp activity and the rates of advection and erosion. The development of legacy landscapes is facilitated by spatial variations in flow convergence that occur in a 2‐D setting but are not captured in idealized 1‐D approaches. The presence of elevated K sn and high relief, advection‐parallel interfluves beyond the region of active rock uplift likely reflects the horizontal advection component inherent to convergent orogenic systems. Key Points: The process of rock advection over midcrustal ramps in convergent orogens is preserved in the geomorphic record as "legacy landscape" Legacy landscapes are characterized by tapered topography and gradual decline in normalized channel steepness in the direction of advection Legacy landscapes were identified in active fold‐thrust belts such as the Himalaya, Andes and Taiwan